Dick's hair A rhetorical stylistic study (Journal of the College of Basic Education, 2022)
This modest research studied the most important stylistic phenomena in the Diwan of Dik Al-Jin Al-Homsi, and it was presented with an introduction; He dealt with the definition of stylistics linguistically and idiomatically, mentioning in haste the emergence of stylistics among the Arabs and Europeans, with mentioning the most important pioneers of this doctrine among the modernists, and indicating that stylistics is a way to enter the writer's soul, to find out his feelings and what is in himself, and then the research studied the most important stylistic phenomena in the poet's diwan Represented by B - First: - The synthetic level, .. Represented by: A- The informative style B- The constructive style C- The level of the poetic image, which includes: 1- Simile 2- Metaphor 3- Metaphor. Second: Music, which is divided into two parts: a- External music, which includes: 1- Meters 2- Rhymes. B- Inner music, which includes: 1- Anaphora 2- Counterpoint. This research used weight statistics